Hegemoni Tubuh Ideal: Siasat Perempuan Jawa Mempertahankan Tubuhnya Pasca Melahirkan - Hanim, Meysella Al Firdha; Triratnawati, Atik (Umbara, 2024)
Pregnancy and childbirth bring significant biological and psychological changes, requiring the body to adapt. These changes, particularly in body shape, often lead some women to prioritize regaining or maintaining an ideal physical shape after giving birth. Despite the availability of modern biomedical care, Javanese women continue to practice traditional postpartum beauty treatments. This study examines the meanings of beauty and health for postpartum women through traditional practices.Using a qualitative ethnographic approach, the research was conducted in Yogyakarta with three informants—mothers who consistently practice traditional postpartum care. Data were collected through observations, interviews, field notes, and document analysis to understand the cultural practices, behaviors, habits, and interactions of the informants.The findings highlight that traditional postpartum care is instrumental in helping these women maintain physical attractiveness, strengthen their relationships with their husbands, and preserve family traditions. Key practices identified include the use of a gurita, stagen, corset, pilis, jamu beras kencur, and betel leaf decoction. These practices are regarded by the informants as essential for maintaining health and beauty after childbirth.